Computerized power transformer monitoring based on internet of things - A H. Mohamad, Auday; S. Mezaal, Yaqeen; F. Abdulkareem, Seevan (International Journal of Engineering and Technology, 2018)
Distributed transformers are imperative equipment in power networks. Due to large amount of transformers distributed over a widespread area in power electric systems, the data acquirement and condition monitoring is essential concern. In spite of security and automation in plants, industrial environment is relatively critical for machines and humans. This study deals with a safety in industrial condition. A model has been designed to detect dangerous situations like breakdown that is the most essential parameter for occurring leakage current in substation and gas leakage based on faults data source file from distinguished sources. Reached outcome will be executed in IoT (Internet of Things) gateway design, to augment technical implementation with scalability. It consists of Node-MCU, node red server, mosquito server that serves as negotiator amid Node-MCU and node red server and Thingspeak IoT platform. Data processing has been completed at Thingspeak IoT platform so that the monitored quantity can be displayed frequently or at scheduled intervals of time. These processed results have been statistically further analyzed using SPSS software package.Â Â